Thyroid Function, Prevalent Coronary Heart Disease, and Severity of Coronary Atherosclerosis in Patients Undergoing Coronary Angiography. (3rd December 2015) - Ling, Yan; Jiang, Jingjing; Gui, Minghui; Liu, Lin; Aleteng, Qiqige; Wu, Bingjie; Wang, Shanshan; Liu, Xiaojing; Gao, Xin
Abstract : This study investigated if free T4 and TSH concentrations or thyroid function categories were associated with prevalent CHD and the severity of coronary atherosclerosis in a population undergoing coronary angiography. This was a cross-sectional study including 1799 patients who were consecutively admitted and underwent coronary angiography. We evaluated the severity of coronary atherosclerosis using Gensini score. In the entire study population, free T4 level was inversely associated with prevalent CHD (OR = 0.95, 95% CI 0.91–0.99, P = 0.01 ) and the natural log-transformed Gensini score (ln(Gensini score)) ( β = −0.03, 95% CI −0.05–−0.01, P = 0.005 ). The odds of CHD increased gradually across hyperthyroidism, subclinical hypothyroidism, and overt hypothyroidism groups using the euthyroid group as the reference, and the trend is borderline significant (P for trend = 0.051). When comparing to the euthyroid group, ln(Gensini score) of the overt hypothyroidism group was significantly higher (P = 0.009 ), but the trend was not significant (P for trend = 0.08). A significant association of thyroid function with CHD or ln(Gensini score) in euthyroid patients was not observed. The present study demonstrated an association of thyroid function with prevalent CHD and the severity of coronary atherosclerosis in a population undergoing coronary angiography. However, this association was not observed in euthyroid individuals.